Explaining the Gender Gap in Job Satisfaction - Paul Redmond; Seamus McGuinness (Institute of Labor Economics (IZA), 2019)
In general, women report greater job satisfaction than men. The existing literature cannot fully explain the nature of this difference, as the gap tends to persist even when controlling for job characteristics. In this paper, we study job satisfaction using recent data for 28 EU countries. Women, on average, are more satisfied than men and the gap remains even when we account for a wide range of personal, job and family characteristics. However, the gap disappears when we include job preferences, as women place greater importance on work-life balance and the intrinsic desirability of the work.
Keywords: J16; J28; J24; 330; job satisfaction; job preferences; gender